2010
DOI: 10.1130/b30173.1
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of the Bolson sand sheet, New Mexico and Texas, and its archaeological significance

Abstract: The Bolson sand sheet occurs in the Tularosa Valley, New Mexico, and the Hueco Bolson, Texas and consists of two principal eolian sand units. Optically stimulated lumi nescence (OSL) dating provides a new chronol ogy of the sand sheet that relates as well to the formation, preservation, and visibility of the local archaeological record. The lower sand (unit Q2) (44.8 ± 2.9 ka) and the upper sand (unit Q3) (22.2 ± 1.6-5.2 ± 0.3 ka) have a combined thickness of less than 2 m. The Q2 sand is characterized by a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…In the Mescalero Plain in southeastern New Mexico, Hall and Goble (2011) recognize two main periods of sand sheet accumulation: 90e50 ka and 18e5 ka, separated by an argillic paleosol. The Bolson Sand Sheet in southern New Mexico and adjacent areas of Texas accumulated between 40 and 50 ka and 25e5 ka, with historical reactivation (Hall et al, 2010). The detailed record from the Strauss Sand Sheet in southern New Mexico and adjacent areas of Chihuahua (Mexico) comprises 4 main aeolian units.…”
Section: Chihuahuan Desertmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Mescalero Plain in southeastern New Mexico, Hall and Goble (2011) recognize two main periods of sand sheet accumulation: 90e50 ka and 18e5 ka, separated by an argillic paleosol. The Bolson Sand Sheet in southern New Mexico and adjacent areas of Texas accumulated between 40 and 50 ka and 25e5 ka, with historical reactivation (Hall et al, 2010). The detailed record from the Strauss Sand Sheet in southern New Mexico and adjacent areas of Chihuahua (Mexico) comprises 4 main aeolian units.…”
Section: Chihuahuan Desertmentioning
confidence: 99%
“…Aeolian deposits are widespread in the Chihuahuan Desert. The most extensive deposits are sand sheets with areas of coppice dunes such as those developed in the southern Tularosa Valley (NM), the Hueco Bolson, the Mescalero Plain, and the Albuquerque Basin (Hall et al, 2008(Hall et al, , 2010Hall and Goble, 2011). Dune fields include the gypsum dunes at White Sands (Langford, 2003;Kocurek et al, 2007) and the quartzose Samalyuca Dunes in northern Mexico (Dominguez Acosta and Langford, 2008).…”
Section: Colorado Plateau Desertmentioning
confidence: 99%
“…These sources included georegistered surface geology and soils maps (plus the descriptive layers associated with the original base polygon datasets), satellite imagery, information in published literature (e.g. Hawley et al, 1969;Langford, 2000;Castiglia and Fawcett, 2006;Hall et al, 2010), expert knowledge and dedicated verification field sorties. Digital Elevation Models and simple contour maps were used to differentiate high and low relief terrain.…”
Section: Methodsmentioning
confidence: 99%
“…As part of an archaeology study on the Fort Bliss Military Reservation in west Texas, Hall et al (2010) reported optically stimulated lumi nescence (OSL) dates from two backhoe trenches referred to as localities 100 and 200. In both trenches, a sedimentary unit termed "Q3" was designated based on soil morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Within this trench, at locality 100a, there are three OSL dates in the lower part of the unit designated Q3 that are older than Organ, two dates at locality 100b that are older, and one date at locality 200 that is older. Based on these dates and soil morphology, Hall et al (2010) made several broad-scale conclusions important for understanding the archaeology record as impacted by late Quaternary environmental change. However, three of their conclusions are not supported by the following sedimentologic, radiocarbon, isotopic, or pedologic evidence, which have implications for similar studies of terrestrial responses to climate change in other arid regions.…”
Section: Introductionmentioning
confidence: 99%